The determinants of profitability (return on equity) among selected commercial banks in Malaysia / Ashsyahira Nasha Abd Latiff - Abd Latiff, Ashsyahira Nasha (2017)
The main purpose of this paper is to analyze the determinants of the profitability ( ROE) among selected commercial banks' profit in Malaysia. A total of 7 licensed commercial banks are chosen to represent the commercial banks in Malaysia during the time line from 2010 to 2016. The dependent variable is Return on Equity and main independent variable is Loan-loss Provision (LLP), Non-performing Loan (NPL) and deposits (DEPO). Panel Data was used to deal in measuring the relationship of the variables. The data also compromised seven year period and consist 7 commercial banks in Malaysia. Statistical tests included normality, stationary and regression test to ensure this study is able to answer the research question. The finding disclose that loan-loss provision and deposits has strong relationship with profitability of the commercial banks in Malaysia while non-performing loan has no positive or negative effect towards the profitability of the commercial banks.